A novel multiple sex chromosome system in Orthoptera, found in the tree cricket Oecanthus rubromaculatus Zefa, 2022 (Grylloidea, Oecanthidae) - Zefa, Edison; Acosta, Riuler Corrêa; Kretschmer, Rafael; Timm, Vítor Falchi; Silva, Anelise Fernandes E; Adamoli, Jailson Vieira; Szinwelski, Neucir; Costa, Maria Kátia Matiotti Da (Zootaxa, 2024)
The X0♂/XX♀ sex chromosome system prevails in most Orthopteran species. The X chromosome stands as one of the largest chromosomes within the complement, and is characterized by its heterochromatic nature. Variations of this model were found in some species of grasshoppers, crickets, and katydids, based on X/autosome rearrangements, giving rise to new sex chromosome systems, such as neo-XY♂/XX♀ and neo-X1X2Y♂/X1X1X2X2♀. The sex chromosome system neo-X1X20♂/X1X1X2X2♀ is rare in Orthoptera, and was observed only in two cricket species. In this study, we present the first multiple chiasmatic sex chromosome system in Orthoptera, found in the tree cricket Oecanthus rubromaculatus Zefa, 2022 from two distinct locations in the State of Rio Grande do Sul, Brazil. In one location, individuals exhibited a karyotype with 2n = 12, X1X2Y1Y2♂/X1X1X2X2♀, while in the other a karyotype of 2n = 12, X1X2X3Y1Y2Y3♂/X1X1X2X2X3X3♀ was observed. We proposed a model to explain the evolutionary steps in the formation of these karyotypes, based on chromosomal information of the Neotropical Oecanthus’ species. In this context, we proposed a hypothesis to explain the chromosome reorganization in O. rubromaculatus, starting from an ancestral karyotype of 2n = 21, X0♂, like the karyotype found in Oecanthus pictus Milach & Zefa, 2015, resulting in a significant reduction to 2n = 12 in O. rubromaculatus. This reorganization has led to the emergence of the novel multiple sex chromosome system in Orthoptera.